The Relationship Of Self Efficacy With The Implementation Of Clean And Healthy Living Behavior (CHLB) In Households In Tallo Village, Makassar City - Jamal, Syamsinar; Indri Primadianty; Ince Annisah Adawiyah Arifin (Indonesian Journal of Wiyata Health Administration (IJWHA), 2024)
What individuals must have to be able to implement clean and healthy living behavior (CHLB) is self-efficacy, without self-efficacy their motivation to change will be hampered, individuals who have high self-efficacy tend to have healthier behavior. The aim of this research is to determine the relationship between self-efficacy and the implementation of clean and healthy living behavior (CHLB) in households in Tallo Village, Makassar City. The type of research used is quantitative research with a cross sectional study approach. The population in this study was all 370 households in RW 4, Tallo Village, Makassar City. The data analysis method uses univariate and bivariate tests with the chi-square correlation test.This research shows that self-efficacy is not very related to a person's desire to adopt clean and healthy living behavior. This means that someone who has high self-efficacy does not necessarily want to adopt clean and healthy living behavior.